PENGARUH PERSEPSI PELAKU UMKM TENTANG AKUNTANSI, PENGETAHUAN AKUNTANSI, DAN SKALA USAHA TERHADAP PENGGUNAAN INFORMASI AKUNTANSI DI KELURAHAN JALAN BARU KECAMATAN PARIAMAN TENGAH KOTA PARIAMAN SUMATERA BARAT TAHUN 2015-2019 - Rini Afrianti; Chandra Halim (MABIS: Jurnal Manajemen Bisnis Syariah, 2021)
This study aims to determine the Effect of Education Level, Accounting Knowledge, Business Scale and Business Experience on Accounting Information in the Village of Kampung Baru City Central Pariaman as many as 24 perpetrators of UMKM consist of one person owner and two employees . Methods of taking samples pe nelitian using Total Sampling. The data collection technique used a questionnaire . Validity and reliability test . The data analysis technique used multiple linear regression , t test, f test, and the coefficient of determination.The results of the research have demonstrated that : (1) not found the influence persespi perpetrators of UMKM to use information accounting . It is proved the value of t count < t table ( 0.449 < 1.6675 ) and the value of sig. 0.619 ( 0.619 > 0.05), (2) there is no effect of accounting knowledge on the use of accounting information . This is evidenced by the value of t count < t table ( 0.486 < 1 , 6675 ) and the value of sig. 0.629 ( 0.629 > 0.05), (3) there is an effect of business scale on the use of accounting information . Ha l is evidenced nila i t count > from t table ( 6.745 > 1.667 ) and the value of sig. 0, 000 (0, 000 < 0 , 05 ), (4) there is an influence on the perception of UMKM actors about accounting , accounting knowledge , and business scale on the use of accounting information . This is evidenced by fish with a calculated F value > F table ( 15.245 > 2 , 74 ) with a sig. 0.000 is less than 0.05 (0.000 <0.05).